The Meaning of Andragogy for Lecturers in The Context of Project-Based Learning in Higher Education - Virdaus, Varia Virdania; Purwoko, Budi; Rosyanafi, Rofik Jalal (Journal of Development Research, 2025)
This study explores how lecturers across five departments at Narotama University—Early Childhood Education (PG PAUD), Civil Engineering, Economics and Business, Computer Science, and Law—interpret and apply andragogical principles within project-based learning (PjBL). Using a qualitative phenomenological design, data were collected through semi-structured interviews with five purposively selected lecturers who had at least two semesters of PjBL experience. Thematic analysis revealed four major themes: (1) the shifting role of lecturers from information transmitters to facilitators; (2) increased student autonomy and engagement; (3) challenges related to students’ readiness for self-directed learning; and (4) the role of reflection in lecturers’ professional growth. The findings indicate that while andragogy aligns strongly with PjBL, its implementation is highly contextual, requiring adaptations based on disciplinary demands and student characteristics. This study contributes to the discourse on contextualized andragogical practice in higher education, highlighting implications for lecturer training, curriculum design, and institutional policy.